Annealing Effects on Photocatalytic Activity of Zn0.2Cd0.8S Films Prepared by Chemical Bath Deposition. (3rd July 2014) - Chai, Yi-Feng; Wang, Ling-Ling; Huang, Gui-Fang; Huang, Wei-Qing; Zhu, Yan-Hua
Abstract : Zn0.2 Cd0.8 S alloyed films were prepared on glass substrates at room temperature using chemical bath deposition method. The obtained films were annealed at temperatures ranging from 200°C to 500°C with heating rate of 5°C/min and annealed at 400°C with heating rate of 2°C/min and 10°C/min. The films were characterized by X-ray diffraction, scanning electron microscopy, energy-dispersive spectroscopy, and UV-VIS spectrophotometer. The increasing of annealing temperature increases the crystallinity and the mean grain size of Zn0.2 Cd0.8 S alloyed films and significantly enhances the absorption in the visible region. The efficient visible light photocatalytic activity for annealed Zn0.2 Cd0.8 S alloyed films is associated with the larger size grain and the higher crystallinity.